PENGARUH LOCUS OF CONTROL, SKEPTISISME PROFESIONAL, DAN KECERDASAN EMOSIONAL TERHADAP KUALITAS AUDIT - Iza Afidati, Novi; Yuniarti, Rita (Penerbit Lafadz Jaya, 2025)
This study aims to analyze the influence of locus control, professional skepticism, and emotional intelligence on Audit Quality (an empirical study at Public Accounting Firms in the Bandung area). This research uses primary data and employs a questionnaire for data collection. The sampling technique used is purposive sampling, involving 67 auditors from 21 Public Accounting Firms. The data collection method is a survey by directly distributing questionnaires to respondents, and the analysis method uses multiple linear regression analysis. The results of this study indicate that locus of control, professional skepticism, and emotional intelligence have a significant effect on audit quality.